2010
DOI: 10.4049/jimmunol.0900416
|View full text |Cite
|
Sign up to set email alerts
|

BTN1A1, the Mammary Gland Butyrophilin, and BTN2A2 Are Both Inhibitors of T Cell Activation

Abstract: Butyrophilin (BTN) genes encode a set of related proteins. Studies in mice have shown that one of these, BTN1A1, is required for milk lipid secretion in lactation, whereas butyrophilin-like 2 is a coinhibitor of T cell activation. To understand these disparate roles of BTNs, we first compared the expression and functions of mouse Btn1a1 and Btn2a2. Btn1a1 transcripts were not restricted to lactating mammary tissue but were also found in virgin mammary tissue and, interestingly, spleen and thymus. In confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
124
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 50 publications
6
124
1
Order By: Relevance
“…The identification of these B30.2 interactors will be necessary to dissect the immunoregulatory mechanisms associated with the engagement of BTN3/CD277 molecule at the surface of T cells versus NK cells. Smith et al demonstrated that BTN1A1 and BTN2A2-Fc fusion proteins bound to activated T cells [22]. Immobilized BTN1A1 and BTN2A2-Fc fusion proteins inhibit the proliferation of murine CD4 1 …”
Section: Discussionmentioning
confidence: 99%
“…The identification of these B30.2 interactors will be necessary to dissect the immunoregulatory mechanisms associated with the engagement of BTN3/CD277 molecule at the surface of T cells versus NK cells. Smith et al demonstrated that BTN1A1 and BTN2A2-Fc fusion proteins bound to activated T cells [22]. Immobilized BTN1A1 and BTN2A2-Fc fusion proteins inhibit the proliferation of murine CD4 1 …”
Section: Discussionmentioning
confidence: 99%
“…The butyrophilins are part of the immunoglobulin superfamily and contain two folded immunoglobulin domains, a transmembrane domain and a C-terminal end that may include a large B30.2 domain. In addition to its role in the MFGM, butyrophilin1A1 has been found to be expressed within the thymus; other butyrophilins are more widely expressed among tissues (Smith et al, 2010a). Butyrophilins and related proteins of the immunoglobulin superfamily appear to play a role in the regulation of proliferation, cytokine secretion and activity of T-cells, and butyrophilin1A1 retains this function, at least in vitro (Smith et al, 2010a).…”
Section: Caseinsmentioning
confidence: 99%
“…In addition to its role in the MFGM, butyrophilin1A1 has been found to be expressed within the thymus; other butyrophilins are more widely expressed among tissues (Smith et al, 2010a). Butyrophilins and related proteins of the immunoglobulin superfamily appear to play a role in the regulation of proliferation, cytokine secretion and activity of T-cells, and butyrophilin1A1 retains this function, at least in vitro (Smith et al, 2010a). It is interesting that butyrophilin1A1 is the only butyrophilin that appears to bind XOR via its B30.2 domain, and it is this binding that is believed to be critical to MFG secretion from lactocytes (Jeong et al, 2009).…”
Section: Caseinsmentioning
confidence: 99%
“…BTN1A1 is predominately expressed in mammary gland and at low levels can be detected in several tissues, such as spleen, thymus, small intestine, and so forth (6). BTN2A2 is broadly expressed in lymphoid and nonlymphoid organs, and both BTN1A1 and BTN2A2 are expressed by thymic stromal cells (6).…”
mentioning
confidence: 99%
“…The BTN2 and BTN3 groups comprise three genes each: BTN2A1, BTN2A2, BTN2A3 and BTN3A1, BTN3A2, BTN3A3, respectively (6).…”
mentioning
confidence: 99%